The combined action of the Nisin and Lactoperoxidase system activation on the microbiological quality of raw milk with special emphasis against E.coli O157H7 in milk: Zina Saab Khudhir and Safwa Mustafa Hammad - Khudhir, Zina Saab (The Iraqi Journal of Veterinary Medicine, 2017)
Escherichia coli O157:H7 were isolated from 90 bovine and ovine locally produced soft cheese samples and their identification were confirmed based on the cultural, biochemical reactions and serological properties, E.coli O157:H7 isolates obtained by plating on the Chromogenic agars. They were further tested serologically for the presence of both O157 and H7 antigenes using the agglutination test kit. The highest non-significant prevalence (P>0.05) level of E.coli O157:H7 was found in the ewe’s soft cheese samples (37.77%) followed by the cow’s soft cheese samples (31.11%). The antimicrobial potency of the Nisin against the sensitive Lactobacillus strain was lost after (10) minutes of heating at (80°C) while retaining (100%) of its antimicrobial potency after its exposure to the pasteurization time and temperature (63°C/ 30 min.). The highest antimicrobial potency of Nisin was achieved at neutral pH (100%) while 90% and 45% of its potency were retained under acidic (pH=3) and alkaline (pH=9) conditions respectively. Nisin had short bacteriocidal incubation period against the sensitive lactobacillus strain where its antimicrobial potency reduced after 48 hours and lost after 120 hours of refrigeration storage period. E.coli O157:H7 was insensitive to the action of Nisin while stressed E.coli O157:H7 by activation of lactoperoxidase system in pasteurized milk was susceptible to its action and such result gave an indication of the synergistic effect of Nisin with activated lactoperoxidase system.